Navigating Industry 4.0: Leveraging additive technologies for competitive advantage in Colombian aerospace and manufacturing industries - Thomas Tegethoff; Ricardo Santa; Juan Manuel Bucheli; Benjamin Cabrera; Annibal Scavarda (PLoS ONE, 2025)
Industry 4.0 initiatives aim to improve competitive advantage. Additive technologies are a technological innovation and have great potential in a developing country like Colombia, The study analyzes how additive technologies, strategies, and process innovation interact to generate positive results, measured by the achievement of operational effectiveness in the aerospace sector and the manufacturing industry in general. Furthermore, the study explores the integration of additive technologies within the framework of Industry 4.0, focusing on the Colombian aerospace and manufacturing sectors. It investigates how these technologies, strategies, and process innovation contribute to operational effectiveness. Data were collected using a Likert-style questionnaire, developed based on established models of innovation framework and operational effectiveness model994 responses were obtained, of which 945 were deemed usable (423 from manufacturing and 522 from aerospace sectors). The analysis involved confirmatory factor analysis (CFA) and structural equation modeling (SEM) using SPSS and AMOS software, ensuring robustness through indicators like Cronbach’s Alpha and fit indices. The study compared findings across the two sectors to highlight differences in how additive technologies influence organizational outcomes. Initial results reveal that while additive technologies significantly enhance process innovation across sectors, their direct impact on operational effectiveness is evident only in the aerospace industry. The findings underscore that the aerospace sector benefits from additive technologies due to their need for complex, high-quality, and small-batch production, emphasizing their role in fostering precision and customization. However, the lack of impact in the manufacturing context is attributed to limited strategic alignment and inadequate implementation practices. Moreover, the results indicate that process innovation is a critical mediator, facilitating the translation of technological advancements into improved operational outcomes. Despite moderate correlations between strategies and operational effectiveness in manufacturing, aerospace organizations exhibit more substantial strategic alignment due to stringent performance demands. These findings highlight the importance of fostering a culture of innovation, adapting organizational strategies, and addressing structural challenges to maximize the benefits of additive technologies. The study contributes to understanding the differential adoption of Industry 4.0 technologies in developing economies, with implications for enhancing competitiveness and sustainability in global markets.